2015
DOI: 10.1007/s00125-015-3774-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced expression of the homeotic transcription factor Prep1 is associated with histone post-translational modifications in skeletal muscle

Abstract: These studies indicate that HG exposure induces NF-κB recruitment and histone modification at the Prep1 5' region, thereby enhancing the transcription of Prep1 and repressing that of Glut4. Histone changes at the Prep1 gene may contribute to insulin resistance in individuals with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
(57 reference statements)
2
23
0
1
Order By: Relevance
“…This is intriguing because human endothelial cells stimulated by hyperglycemia alters the subcellular locality and this is associated with distinguishable histone and non-histone regulatory events. While these (33,51) and other studies indicate biochemical properties as a glycemic sensor (52), nuclear accumulation with specific nucleosomal preferences highlights dynamic Set7 activity. This fascinating link with extracellular signaling also carries with it precise instructions for Set7 activity that include broad substrate specificity (30).…”
Section: Discussionmentioning
confidence: 81%
“…This is intriguing because human endothelial cells stimulated by hyperglycemia alters the subcellular locality and this is associated with distinguishable histone and non-histone regulatory events. While these (33,51) and other studies indicate biochemical properties as a glycemic sensor (52), nuclear accumulation with specific nucleosomal preferences highlights dynamic Set7 activity. This fascinating link with extracellular signaling also carries with it precise instructions for Set7 activity that include broad substrate specificity (30).…”
Section: Discussionmentioning
confidence: 81%
“…Knockdown of SET7 in a hyperglycemia model reduced the induction of oxidant and inflammatory pathways. In a related publication on Prep1 , a gene exerting major effects on the insulin sensitivity of glucose transport, it was shown that high glucose (HG) exposure induces NF-κB recruitment and histone modification at the Prep1 5′ region 168 . HG exposure also resulted in the recruitment of EP300 and SET7 (which was confirmed by an increase in H3K9/14 acetylation and H3K4me/me2) at the Prep1 promoter.…”
Section: Metabolic Diseasesmentioning
confidence: 94%
“…SET7 is reported to have multiple roles in diabetes and related diseases 168-172,180 . Perhaps one of the underlying mechanisms is due to SET7 methylation of HIF-1α at K32 and HIF-2α at K29 180 .…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Accumulation of lipids that occurs in AT during obesity triggers an inflammatory response that results in an increased secretion of several inflammatory cytokines (Haase et al, 2014;Raciti et al, 2017). Such molecules can also activate JNK and NF-κB signaling pathways in the liver and skeletal muscle, thus inhibiting systemic insulin signaling (Hotamisligil et al, 1993;Ciccarelli et al, 2016).…”
Section: Molecular Pathways Linking Obesity-induced Inflammation and Irmentioning
confidence: 99%